PENERAPAN SANKSI PIDANA TAMBAHAN PENGGANTIAN KERUGIAN KEUANGAN NEGARA PADA TINDAK PIDANA KORUPSI - Sefyanda, Lenny (Universitas Ekasakti, 2019)
Additional criminal sanctions for compensation for state finances are regulated in Article 18 of Act Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The maximum payment of substitute money is the same as the property obtained from the crime of corruption, so to determine the amount of substitute money must be calculated in advance how much money the state has taken by the defendant for his personal interests. In practice, the provision has been applied by the Judge in the case of corruption in the procurement of clothing and sports shoes at the Payakumbuh City Education Office as in Decision Number 16 / Pid.Sus-TPK / 2015 / Pn.Pdg,